Dynamics of silver nanoparticles at the solution/biofilm/mineral interface. Issue 10 (4th September 2018) - Desmau, Morgane; Gélabert, Alexandre; Levard, Clément; Ona-Nguema, Georges; Vidal, Vladimir; Stubbs, Joanne E.; Eng, Peter J.; Benedetti, Marc F.
Abstract : For the first time, a quantitative distribution of AgNPs at the biofilm/mineral interface was obtained using LP-XSW-FY. Abstract : The extensive use of silver nanoparticles (AgNPs) is likely to result in their significant environmental release, and thus raises important concerns regarding their impact on ecosystems. In soils, bacterial biofilms can be found as mineral coatings, which form a complex interface that exhibits highly specific physico-chemical properties. As a result, this environmental compartment is likely to partially control the fate of AgNPs. However, the interaction modes that nanoparticles undergo at the solution/biofilm/mineral interface are not yet well understood. Thus, herein, the dynamics of the AgNP interactions at the Shewanella oneidensis MR-1 biofilm-corundum (α-Al2 O3 ) interface were investigated via long-period X-ray standing waves fluorescence yield spectroscopy. Three different nanoparticle coatings with various properties (PVP, SiO2 and SiO2 –NH2 ) are investigated, which demonstrate important differences in the partitioning and stability of AgNPs at this complex interface. The behavior of the two AgNPs coated with an organic layer, but with opposite charges (SiO2 and SiO2 –NH2 ), indicates that initially, electrostatic interactions control the AgNPs partitioning at the solution/biofilm/mineral interface. In addition, the comparative study of the organic PVP-coated and the inorganic SiO2 -coated AgNPs, which are both negatively charged, highlights the control imposed by the nanoparticle size and hydrophobic properties on their interactions with this complex interface.